Implementasi Noise Removal Dan Image Enhancement Pada Citra Digital Menggunakan Metode Adaptive Median Filter - Nisa Fachrunnisa; Ari Usman; Mufida Khairani (Jurnal Ilmu Komputer dan Sistem Informasi, 2024)
Image as a multimedia component plays a very important role as a form of visual information. Images have characteristics that text does not have, namely images that are rich in information. Even though an image is rich in information, the image we have often experiences image degradation, namely a decrease in image quality, for example because it contains defects or noise. The Adaptive Median Filter (AMF) method is a method designed to eliminate problems that arise. faced with a standard median filter. Adaptive median filter has a dual purpose, namely removing impulse noise in the image and reducing distortion in the image. This filter also smooths out noise. Therefore, the author is interested in "Implementing Noise Removal and Image Enhancement in Digital Images Using the Adaptive Median Filter Method". This is done in order to find out the results of improving the quality of the noised image. The output that will be produced in this final project is that the author discusses how an image that initially has good quality is then given noise, then a filtering process is applied using the adaptive median filter method and the image quality is improved using image enhancement. Keywords: AMF, Image, Results, Noise